Analisis Kemampuan Mengapresiasi Puisi Aku Karya Chairil Anwar pada Siswa Kelas VIII Sekolah Menengah Pertama - Abu Bakar Tumpu; Wiwin Kaswati; Erniati Erniati (AIJER: Algazali International Journal Of Educational Research, 2021)
Abstract: An Analysis of The Ability to Appreciate My Poems By Chairil Anwar pthere are Class VIII Studentsof Junior High School. This study aims to describe the ability to appreciate the poetry Aku by Chairil Anwar in grade VIII junior high school students. Approach to qualitative research with caulitative descriptive research penis. The pupulation in this study was 288 students of SMPN 36 Makassar City spread across 9 classes. The sample was determined to be 32 students, of which there were 12 women and 15 men. Teknik data collection in the form of tests. As for the data analysis techniques used in this study, namely quantitative descriptive analytical techniques. Based on the results of the study, it can be seen that the ability of students to appreciate poetry was 26 people or 81% who obtained a score of 75 and above, with an average score of 85.28% (Very good) and in terms of all aspects of physical elements there were 23 people or 71% who obtained a score of 75 and above with an average score of 81.18% (Very good). Thus the ability to appreciate poetry in class VIII Sstudents of Junior High School ecolah is sufficient.